Q-bot: heavy object carriage robot for in-house logistics based on universal vacuum gripper. (16th February 2020) - Matsuo, Isamu; Shimizu, Toshihiko; Nakai, Yusuke; Kakimoto, Masahiro; Sawasaki, Yuki; Mori, Yoshiki; Sugano, Takamasa; Ikemoto, Shuhei; Miyamoto, Takeshi
Abstract : Q-bot is the human-sized carriage robot for lifting heavy weight objects of in-house logistics, such as storehouse and convenience store. The main feature of Q-bot is the adhesion mechanism beneath the foot, called the turnover prevention Universal Vacuum Gripper (in short TP UVG) that holds its body for turnover prevention and self-weight compensation. Turnover prevention is one of the key technologies of in-house logistic robot for effective use of it. Self-weight compensation is another clue for the robot to achieve the labor work in narrow space. TP UVG is achieved both functions by adhering to uneven ground. The other function of Q-bot is multiple objects graspability based on two-sized Universal Vacuum Gripper by dual-armed manipulation. Q-bot also has omnidirectional movability based on mecanum wheels. In this research, we will report on the development of Q-bot and experiments to prevent the robot from falling when it grabs a heavy object while attached to the ground. We also report Q-bot demonstrations of Future Convenience-Store Challenge in the World Robot Summit 2018. GRAPHICAL ABSTRACT: